Evaluasi Penerapan Sistem Digitalisasi Pemungutan Pajak Reklame Dalam Meningkatkan Pendapatan Asli Daerah Kota Bekasi Tahun 2024 - Harjo, Dwikora; Nabila, Girotul (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Bekasi City as an autonomous region in West Java Province has great potential in Regional Original Revenue (PAD), one of which is through billboard tax collection. Billboards are media that convey information to the wider community and are installed along roads that contain messages or information. Prior to the implementation of the digitalization system, billboard tax revenue in Bekasi City experienced inconsistencies between target and realization. For this reason, since 2022, the Bekasi City Government began implementing a digital system in billboard tax collection. This study aims to evaluate the implementation of a digitalized billboard tax collection system in increasing Regional Original Revenue (PAD) in Bekasi City in 2024. This research uses William N. Dunn's evaluation theory with the dimensions of effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. This research method uses descriptive qualitative. The results showed that after the implementation of the digitalization system, the effectiveness of billboard tax collection was quite effective, with a realization achievement of 98.95% in 2024, where the tax target and realization also increased. Obstacles found include low understanding and awareness of taxpayers, lack of literacy, and lack of socialization of the system. Efforts made to overcome these obstacles are continuous education, simplifying procedures, and increasing supervision and technical services.